Pengembangan LKPD Cerita Hikayat Bermuatan Toleransi pada Siswa SMA Kelas X - Nila Safina; Mulia Rizki (Universitas Islam Sumatera Utara, 2022)
LKPD is a sheet containing tasks that must be done by students and equipped with instructions or steps to complete the tasks ordered in the activity sheet. The research method used is 4D development. The results obtained from the assessment of material experts were the total score in the first stage of validation was 94 with an average of 4.47 that indicated the